Development and Testing of Runner and Conical Basin for Gravitational Water Vortex Power Plant - Dhakal, Subash; Nakarmi, Susan; Pun, Pikam; Thapa, Arun Bikram; Bajracharya, Tri Ratna (Journal of the Institute of Engineering, 2014)
The Terai region in Nepal has water resources with very low head and medium to high discharge conditions. Hence, the people of the Terai region are not being able to utilize the water resources available near them due to the limitation of technology. This study is intended to serve the purpose of further research of ultra-low head gravitational water vortex turbines useful for power generation in the Terai region. Gravitational water vortex turbine is an ultra-low head turbine which can operate in as low head as 0.7m with similar yield as conventional hydroelectric turbines characterized with positive environmental yield. This study has been carried out in two phases. In the first phase, two different turbines are to designed and fabricated and the performance characteristics of the new turbine are to be compared with that of the installed turbine. The second phase includes the design and fabrication of the conical basin. Experimental tests will be carried out and the performance of the system with the use of a conical basin will compared with that of the system using the cylindrical basin. A site testing also has been carried out to ensure the performance of system. DOI: http://dx.doi.org/10.3126/jie.v10i1.10895 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 140–148